Getting started with FPGAs : digital circuit design, Verilog, and VHDL for beginners - Merrick, Russell (No Starch Press, 2024)
"A straightforward introduction to working with FPGAs. Explores the inner workings of an FPGA and high concepts like state machines, crossing clock domains, and parallel logic. Features hands-on projects and thoroughly annotated code examples in both Verilog and VHDL"--